If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 4)(x + 4) = 88 Reorder the terms: (4 + x)(x + 4) = 88 Reorder the terms: (4 + x)(4 + x) = 88 Multiply (4 + x) * (4 + x) (4(4 + x) + x(4 + x)) = 88 ((4 * 4 + x * 4) + x(4 + x)) = 88 ((16 + 4x) + x(4 + x)) = 88 (16 + 4x + (4 * x + x * x)) = 88 (16 + 4x + (4x + x2)) = 88 Combine like terms: 4x + 4x = 8x (16 + 8x + x2) = 88 Solving 16 + 8x + x2 = 88 Solving for variable 'x'. Reorder the terms: 16 + -88 + 8x + x2 = 88 + -88 Combine like terms: 16 + -88 = -72 -72 + 8x + x2 = 88 + -88 Combine like terms: 88 + -88 = 0 -72 + 8x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '72' to each side of the equation. -72 + 8x + 72 + x2 = 0 + 72 Reorder the terms: -72 + 72 + 8x + x2 = 0 + 72 Combine like terms: -72 + 72 = 0 0 + 8x + x2 = 0 + 72 8x + x2 = 0 + 72 Combine like terms: 0 + 72 = 72 8x + x2 = 72 The x term is 8x. Take half its coefficient (4). Square it (16) and add it to both sides. Add '16' to each side of the equation. 8x + 16 + x2 = 72 + 16 Reorder the terms: 16 + 8x + x2 = 72 + 16 Combine like terms: 72 + 16 = 88 16 + 8x + x2 = 88 Factor a perfect square on the left side: (x + 4)(x + 4) = 88 Calculate the square root of the right side: 9.38083152 Break this problem into two subproblems by setting (x + 4) equal to 9.38083152 and -9.38083152.Subproblem 1
x + 4 = 9.38083152 Simplifying x + 4 = 9.38083152 Reorder the terms: 4 + x = 9.38083152 Solving 4 + x = 9.38083152 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 9.38083152 + -4 Combine like terms: 4 + -4 = 0 0 + x = 9.38083152 + -4 x = 9.38083152 + -4 Combine like terms: 9.38083152 + -4 = 5.38083152 x = 5.38083152 Simplifying x = 5.38083152Subproblem 2
x + 4 = -9.38083152 Simplifying x + 4 = -9.38083152 Reorder the terms: 4 + x = -9.38083152 Solving 4 + x = -9.38083152 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = -9.38083152 + -4 Combine like terms: 4 + -4 = 0 0 + x = -9.38083152 + -4 x = -9.38083152 + -4 Combine like terms: -9.38083152 + -4 = -13.38083152 x = -13.38083152 Simplifying x = -13.38083152Solution
The solution to the problem is based on the solutions from the subproblems. x = {5.38083152, -13.38083152}
| x-(2x+1)-8+3=3-(3x+3) | | 10x+16=86 | | 3x+16=37 | | (10n)7= | | 8-(2x+1)-8+3=3-(3x+3) | | 98-9x=4x+7 | | 3.1+(8.6+m)= | | P=5h+5u | | ((x^2-9)/(x^2+7x+12))/((x^2-4x-32)/(x^2-3x)) | | -4n+18=-2n-18 | | 8x+b+4x= | | 1-3.5t=1.4-2.33t+1.5 | | 3f+4k-5f= | | -5=5t+5 | | 8x^4+35x^2+12=0 | | P=10 | | 0=-5p(-3q)+(4m)(-6n) | | 2/3x+4=-26 | | 10x+27=6+17x | | 2(X+7Y)= | | 5t+5(t+3)=195 | | 8z-51z+15-30z-15z+2z=53z+15+31z+2z-172 | | -10x-7x=10x+24 | | 5x-13x= | | -4.9t^2+179t+12.4=0 | | (1/3)9s | | 5/5*1/2 | | 20*x-3*y= | | 37+x=2(8+x) | | 5(t-3)+7t=6(2t+5)-8 | | 39=6x+3 | | -5+8=m-4 |